2019
DOI: 10.2147/cmar.s198615
|View full text |Cite|
|
Sign up to set email alerts
|

<p>microRNA-548b suppresses aggressive phenotypes of hepatocellular carcinoma by directly targeting high-mobility group box 1 mRNA</p>

Abstract: Background and purpose: An increasing number of studies have revealed that microRNAs (miRNAs) are the main drivers of hepatocarcinogenesis including progression to later stages of liver cancer. Recently, miR-548b was identified as a cancer-related miRNA in glioma and tongue squamous cell carcinoma. Nonetheless, the expression pattern and specific roles of miR-548b in hepatocellular carcinoma (HCC) have not yet been clarified. Methods: Expression levels of miR-548b in HCC tissues and cell lines were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…25 In HCC, miRNA-548b inhibits the invasive phenotypes of HCC cells by interacting with HGMB1. 24 All results point out that miR-548b plays an important role in cancer progression. However, the expression level and potential function of miR-548b in melanoma remain unclear.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…25 In HCC, miRNA-548b inhibits the invasive phenotypes of HCC cells by interacting with HGMB1. 24 All results point out that miR-548b plays an important role in cancer progression. However, the expression level and potential function of miR-548b in melanoma remain unclear.…”
Section: Discussionmentioning
confidence: 96%
“…26,48 Yun et al have demonstrated that miRNA-548b reduces the invasive behaviors of HCC by modulating HMGB1. 24 Lin et al performed an in vitro experiment of HCC cells and provided evidence that HCC cell growth and apoptosis are regulated by miR-548b. 48 Meanwhile, miR- 198 FENG 548-3p is markedly downregulated in breast cancer and overexpression of miR-548-3p inhibits proliferation and promotes the apoptosis of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-548b inhibits cells proliferation and enhances apoptosis in breast cancer [38]. The miR-548b also inhibits proliferation and invasion in malignant glioma [39] and hepatocellular carcinoma (HCC) [40,41]. On the other hand, in esophageal squamous cell carcinoma (ESCC), the miR-548 enhances cell migration and invasion [42].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs do not encode any protein, but can regulate biological processes by inhibiting the expression level of target gene mRNA, thereby regulating the occurrence and progression of the disease (11)(12)(13). Studies have shown that miRNAs are differentially expressed in a variety of cancers, and differentially expressed miRNAs can be involved in the development and progression of cancer (14)(15)(16)(17), including colon cancer (18)(19)(20). For example, the expression level of miR-3653 is significantly downregulated in colon cancer tissues and cells, and the increased expression level of miR-3653 can significantly inhibit the migration and invasion of colon cancer cells by inhibiting the expression level of target gene Zeb2.…”
Section: Introductionmentioning
confidence: 99%